IMPACT OF FEED ON GROWTH AND DEVELOPMENT OF DIFFERENT BROILER-STRAINS - VIVEK PRATAP SINGH; MAYANK DUBEY; K. RAJENDRA PANDEY; A. K. CHAUBEY (The Bioscan, 2013)
An experiment was carried out on three broiler-strains viz- Vencove (B1), Hubbard (B2) and Croiler (B3) at the selected poultry farms in Gorakhpur region with the objective to investigate a suitable feed/ration for local poultry raisers. For this purpose three type of feeds were taken as broiler mash 100 percent (F1) considered as a control group, soybean 30 percent + maize 70 percent (F2) and broiler mash 30 percent + maize 70 percent (F3) supplied to 28000, 35150 and 27250 number of birds in each experimental group, respectively with three replications. Initial average body weight of day old, average feed intake, feed conversion efficiency, body weight gain and mortality of Table birds, was recorded and analyzed. The average feed intake in treatment groups F1, F2 and F3 was estimated 2.26kg, 2.16kg and 2.23kg, respectively, body weight gain in these groups were calculated as 1.07kg, 1.15kg and 1.08kg per bird and the corresponding value for feed conversion efficiency was 1.94kg, 1.76kg and 1.89kg per bird in all the groups, respectively. Results of experiment show F2 feed was the best feed in overall experiment. Feed intake, body weight gain and feed conversion efficiency for all the three treatment groups were found to be highly significant (P<0.01).